CROSSED RENAL ECTOPIA WITH CHRONIC KIDNEY DISEASE - DR.S.SAKTHI SELVA KUMAR; DR.M.V.BHARGAVI; DR.S.PALANIANDAVAN (International Journal of Pharma and Bio Sciences, 2015)
An ectopic kidney is an abnormal localization of a kidney due to a developmental anomaly and it occurs as a result of a halt in the migration of the kidneys to their normal locations during the embryonic period. The asymptomatic, non-complicated cases were mostly managed conservatively, but nephrectomy may be necessary if there are untreatable complications such as stones, infection or trauma. Development of chronic kidney disease in renal ectopia is uncommon. Here we present a case of crossed ectopic kidney in a patient who developed chronic kidney disease.